Japanese short stories for beginners : 20 captivating short stories to learn Japanese & grow your vocabulary the fun way!. ([United States?] : Lingo Mastery, 2020)
" ... In this book we have compiled 20 easy-to-read, compelling and fun stories that will allow you to expand your vocabulary and give you the tools to improve your grasp of the wonderful Japanese language."--Back cover
Train -- Mountaineer -- Secret -- Invention -- Childhood friends -- Elevator -- Hobby -- Hard worker -- Dream -- Crybaby -- A winter morning -- Spam emails -- Lost item -- Annoying neighbor -- Hypothesis -- Marriage -- Cousins -- Essay -- Other lives -- A black car -- Conclusion.
CSE
Text in Japanese and English.
Keywords: Japanese language -- Readers; Short stories, Japanese; Short stories; Japanese language -- Vocabulary; Japanese language -- Study and teaching -- English speakers; Reading comprehension -- Study and teaching -- English speakers